Respostas

2013-08-22T16:34:49-03:00
A) F(g(2))
g(x) = 2x - 3
g(2) = 2.2 - 3
g(2) = 4 - 3
g(2) = 1
F (g(2))=1

b) g(h(0))
1º: h(x) = 5x + 4
     h(0) = 5.0 + 4
     h(0) = 4

2º: g(h(0)) = g(4)
     g(x) = 2x - 3
     g(4) = 2.4 - 3
     g(4) = 8 - 3
     g(4) = 5

c) F(h(-1))
    h(x) = 5x + 4
    h(-1) = 5.(-1) + 4
    h(-1) = -5 + 4
    h(-1) = -1

d) h(g(-4))
1º: g(-4)
     g(x) = 2x - 3
     g(-4) = 2.(-4) - 3
     g(-4) = -8 -3
     g(-4) = -11

2°: h(g(-4)) = h(-11)
     h(x) = 5x + 4
     h(-11) = 5.(-11) + 4
     h(-11) = -55 + 4
     h(-11) = -51